Pengaruh Budaya Organisasi dan Gaya Kepemimpinan terhadap Kinerja Pegawai - Fadhilah, Istiyanti Afifah; Azmawaroh Nasution, Dini; Stepy Natalie, Laurensia; Intania Kolin, Ludgardis (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
Along with the birth of various kinds of organizations which certainly have a variety of organizational cultures and leadership styles applied, it will produce different employee performance in each organization, some of which are satisfied, sufficient, or even dissatisfied. Even the leadership style and culture in an organization can reflect how the character of the organization is, whether the system is running optimally or there are still many mistakes that must be corrected. Because basically these two things will greatly affect the sustainability of the organization, especially in the long term, so that these two factors should be considered in the implementation of the management of an organization. Therefore, this study aims to determine the impact of organizational culture and leadership style on employee performance, this research was conducted using the literature review method, with data in the form of 4 scientific journals that have been reviewed. The results obtained show that organizational culture and leadership style have a significant influence on employee performance, it is concluded that the more effective the system used by the organization, it will have a positive impact on employee performance, and vice versa when the organization is unable to implement an effective system and tends to lag behind the times, it will have a negative impact on employee performance.